1991
DOI: 10.1103/physrevlett.67.903
|View full text |Cite
|
Sign up to set email alerts
|

Oscillations with a period of two Cr monolayers in the antiferromagnetic exchange coupling in a (001) Fe/Cr/Fe sandwich structure

Abstract: Oscillations with a period of two Cr monolayers were measured in the antiferromagnetic exchange coupling between Fe magnetizations separated by Cr. The coupling was measured on a sample consisting of a Au(20 A)/Fe(50 A)/Cr(0-18 A wedge) film deposited by a molecular-beam epitaxy on a Fe[lOO] single-crystal "whisker." The Cr and Fe grew monolayer by monolayer as monitored by reflection high-energy-electron diff'raction. The coupling was determined from the magneto-optic Kerr effect. It was antiferromagnetic for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(49 citation statements)
references
References 8 publications
1
48
0
Order By: Relevance
“…Although in most cases, the coupling is of the form (14), which leads to either ferro-or antiferromagnetic coupling, Rűhrig et al [21] found that for spacer thicknesses around a change of sign of J, the interlayer coupling in Fe/Cr/Fe films A great variety of experimental methods have been used to investigate IEC: • The most widely used method consists in measuring magnetization [20,22], magneto-optical Kerr effect (MOKE) [23,24] or magnetoresistance [19] loops. With this method, however, only antiferromagnetic coupling can be measured in general.…”
Section: General Considerationsmentioning
confidence: 99%
“…Although in most cases, the coupling is of the form (14), which leads to either ferro-or antiferromagnetic coupling, Rűhrig et al [21] found that for spacer thicknesses around a change of sign of J, the interlayer coupling in Fe/Cr/Fe films A great variety of experimental methods have been used to investigate IEC: • The most widely used method consists in measuring magnetization [20,22], magneto-optical Kerr effect (MOKE) [23,24] or magnetoresistance [19] loops. With this method, however, only antiferromagnetic coupling can be measured in general.…”
Section: General Considerationsmentioning
confidence: 99%
“…Among them, two dimensional systems such as ultrathin films have been actively studied due not only to a fundamental interest but also to a possibility for application to magnetic and magneto-optic storage technologies. Fe and Cr multilayer with body centered cubic (bcc) lattice is well known as the typical system for giant magnetoresistance (GMR) device, showing an in-plane magnetic anisotropy and an oscillatory interlayer magnetic coupling [1][2][3][4]. In contrast to this, Fe films with face centered cubic (fcc) lattice can be stabilized on Cu(001) substrate [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 92%
“…The situation became even more complicated after more refined experiments on samples having a considerably improved crystalline quality. From these it appeared that in addition to the above-mentioned long period oscillations also oscillations were present with very short periods down to 2 monolayers (MLs) for Cr and Mn (100) spacers [19,20], i.e. the exchange coupling displayed a socalled multiperiodic coupling behavior.…”
Section: Experimental Observations Hisorymentioning
confidence: 99%